Longer prime presentation decreases picture–word cross-domain priming - Miyoshi, Kiyofumi; Kimura, Yusuke; Ashida, Hiroshi (Frontiers in Psychology, 2015)
A short prime presentation has been shown to provide a greater priming magnitude, whereas a longer prime presentation results in a lower priming magnitude. In Experiment 1, we attempted to replicate the decrease of priming using word stimuli. Words were presented in both prime and test sessions, and participants judged whether each stimulus was natural or manmade. In Experiment 2, we employed a cross-domain priming paradigm to assess the impact of prime duration on non-perceptual processes. Pictures were presented in prime sessions, and their semantically matched words were presented in test sessions. We did not observe a significant decrease in priming in Experiment 1. However, we found that 2000 ms of prime exposure led to weaker cross-domain priming when compared with 250 ms of the exposure in Experiment 2. The results suggest that the longer presentation of pictures causes a non-perceptual adaptation effect. This effect may occur at conceptual, linguistic, and/or response-related levels.